Light-Field-Driven Current Control in Dielectrics with pJ-Level Laser Pulses at 80 MHz Repetition Rate - Hanus, Vaclav; Csajbok, Viktoria; Papa, Zsuzsanna; Budai, Judit; Marton, Zsuzsanna; Kiss, Gellert Zsolt; Sandor, Peter; Paul, Pallabi; Szeghalmi, Adriana; Wang, Zilong; Bergues, Boris; Kling, Matthias F.; et al. (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Solid-state devices capable to react on the sub-cycle evolution of optical fields can pave the way towards petahertz electronics or provide new diagnostic devices for few-cycle lasers [1]. Such devices might rely on an effect of a transient metallization of wide-bandgap materials demonstrated in dielectrics [2] and semiconductors [3]. The observation of optical current control so far has been limited to millijoule-class laser systems which hinders the development towards the miniaturization and mass availability of the potential devices as these high-pulse-energy systems are bulky and have low repetition rate. Here, we report on the transient metallization and CEP-driven current control induced in a compact setup at 80 MHz repetition rate in dielectric SiO 2, HfO 2 and semiconducting GaN with pJ-class pulses for the first time to our knowledge.
CRIS-Team Scopus Importer:2023-04-20